Pengaruh Pemberian Slimber Ice terhadap Intensitas Rasa Haus Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di RS Santa Elisabeth Medan Tahun 2024 - Lindawati Farida Tampubolon; Agustaria Ginting; Clarita Famatirani Margareta El. Hia (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Chronic kidney failure patients experience excess fluid, so fluid restrictions are needed. Fluid restrictions in hemodialysis patients cause dry mouth. The dry mouth experienced by the patient can cause high thirst, high thirst can cause non-compliance with a fluid restricted diet. As a result of limiting fluid intake carried out ini hemodialysis patients, it results in a feeling of thirst which causes the patient to have the desire to drink. The aim of this study is to determine the effect of giving slimber ice on the intensity of thirst in patients with chornic kidney failure undergoing hemmodialysis. This research uses one group pretest-posttest design. The sampling technique is purposive sampling with a total of 20 respondents. The instrument used in this research is the Visual Analogue Scale fo Assessment of Thirst Intensity. The research results showed that the average thirst intensity score of patients with chronic kidney failure undergoing pre-intervention hemodialysis was 4.80, standard deviation 1,936, and post test intervention 3.10,, standard deviation 1,410. The result of statistical tests show that there is an effect of giving slimber ice on the intensity of thirst in patients with chronic kidney failure undergoing hemodialysis. The results of the paired t-test, obtain p value = 0.001. This intervention can be a form of therapeutic management that can be applied to reduce complaints of thirst at home or in hospital.